IMPLEMENTASI KEBIJAKAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI DI KELURAHAN MAMBORO KECAMATAN PALU UTARA - Fauzan, Ahmad (Katalogis, 2014)
This research is aimed at analyzing the implementation of the national program forstrengthening their self-funded community. In addition, it is also aimed at analyzing factors both hampering and supporting the implementation of the national programs for community self- empowerment at the village of Mamboro. The research method applied is descriptive-qualitative. The Informan of this research are The Leader Of PNPM Unit, The Village Chief of Mamboro And Mamboro Barat, The BKM Nadoli member, The Village Supervisor, and The Targeting People. The types of data are primary data and secondary data. The data of the study is obtained through observations, interviews, and documentation. The result of the study indicates that the implementation of PNPM policy has run well although some hampering and supporting factors still take place during the period of the policy implemtation.